Dinamika Dinamika konflik dan Sunni Syiah pada Era Dinasti Safawiyah: Dinamika konflik dan Sunni Syiah pada Era Dinasti Safawiyah - Muhammad Kautsar Thariq Syah; Putri Lailatus Sa’adah; Yan Nurcahya Nurcahya (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
The Safavid Empire was founded when the Ottoman Empire reached its peak in Turkey. Geographically, the territory controlled by the Safavid Empire included most of modern Persia, areas in Iraq, the Caucasus, and parts of Central Asia. Safi al-Din founded the Safavid Order after replacing his teacher and father-in-law who died in 1301 AD. In 1508–1509 AD, Shah Ismail I succeeded in conquering Baghdad and most of the southwestern region of Persia. Shah Ismail I began to carry out large-scale attacks on Sunni Muslims and destroyed Sunni mosques and tombs. Since the reign of Sultan Salim I, the jihad movement has moved westward (Europe) to the eastern region which is known as the Islamic region where the Shia sect spread, namely the Iraq and Asia Minor Conflicts until the real conflict between the two dynasties. Keywords: Conflict, Sunni, Shia, Safavid